Resilience and Vulnerability: Neurodevelopment of Very Preterm Children at Four Years of Age - Young, Julia M.; Vandewouw, Marlee M.; Whyte, Hilary E. A.; Leijser, Lara M.; Taylor, Margot J. (Frontiers in Human Neuroscience, 2020)
Children born very preterm (VPT) are at high-risk for altered brain development and impaired neurodevelopmental outcomes but are not well studied before school-age. We investigated 64 four-year-olds: 37 VPT children (<32 weeks gestational age [GA]; 22 males; mean GA: 28.8 weeks ± 1.6), 25 full-term (FT) children (12 males), plus two VPT cases with ventriculomegaly and exceptionally resilient outcomes. All children underwent high-resolution structural magnetic resonance imaging and developmental assessments. Measures of brain volume, cortical thickness, and surface area were obtained. Children born VPT demonstrated reduced cerebral and cerebellar white matter volumes yet increased cerebral grey matter, temporal lobe, occipital lobe and ventricle volumes after adjusting for total brain volume. Cortical thickness was greater in the VPT children compared to FT children across all lobes. On developmental assessments, the VPT children scored lower on average than FT children while the two cases had intact cognitive abilities. In addition to larger ventricle volumes, the two cases had white matter and grey matter volumes within the ranges of the FT children. The VPT children displayed distinct differences in structural brain volumes at 4 years of age, consistent with delayed maturation. The cases with persistent ventriculomegaly and good cognitive outcomes displayed typical grey matter and increased white matter volumes, indicating a potential protective developmental phenomenon contributing to their intact cognitive abilities.